Penetrating an Isolated Market - Abutalib Manouchehr Arabi; Imam Mahdi (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2026)
This article examines the Indonesian government's interest in signing the Indonesia-Iran Preferential Trade Agreement (II-PTA) on May 23, 2023, at the Bogor Presidential Palace. Using a descriptive qualitative approach and Nuechterlein's national interest theory framework as well as the concept of political economy, this research analyzes the economic and political dimensions underlying the decision. The research findings indicate that Indonesia's interests in the II-PTA are multidimensional: first, economic interests such as diversifying export markets to non-traditional regions, eliminating and reducing tariffs on 239 tariff lines, and the opportunity to utilize Iran as a gateway to the Middle East, Central Asia, South Asia, and Europe thru the International North-South Transport Corridor (INSTC); second, geopolitical interests in strengthening Indonesia's diplomatic position and maintaining an independent foreign policy of an active and independent stance; and third, interests from the perspective of international trade in the form of selective trade liberalization that enhances the competitiveness of Indonesian products in the Iranian market. With an export value projected to reach USD 494 million by 2030, the II-PTA is a strategic instrument for Indonesia to strengthen national economic resilience amid the dynamics of the global trade war.